2023
DOI: 10.1186/s13058-023-01697-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose aspirin, statins, and metformin and survival in patients with breast cancers: a Norwegian population-based cohort study

L. Lukas Löfling,
Nathalie C. Støer,
Bettina Kulle Andreassen
et al.

Abstract: Background Previous studies assessed the prognostic effect of aspirin, statins, and metformin in breast cancer (BC) patients, with inconclusive results. Methods We performed a nationwide population-based cohort study to evaluate if post-diagnostic use of low-dose aspirin, statins, and metformin was associated with BC-specific survival. Women aged ≥ 50 years and diagnosed with BC in 2004–2017, who survived ≥ 12 months after diagnosis (follow-up star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…One study in patients with type 2 diabetes that evaluated different cancers did not find that effect of metformin on overall cancer risk; however, when they evaluated different cancers separately, they did observe a modest reduction in breast cancer with an incidence rate ratio of 0.77 (95% CI:0.43; 1.40) [ 91 ]. The use of metformin after a cancer diagnosis has also been shown to decrease the risk of breast cancer-specific death [ 92 ]. An early meta-analysis of observational studies found that metformin decreased breast cancer risk in postmenopausal women with diabetes compared to those on other antidiabetic therapies [ 11 ].…”
Section: Translating Metformin To the Clinicmentioning
confidence: 99%
“…One study in patients with type 2 diabetes that evaluated different cancers did not find that effect of metformin on overall cancer risk; however, when they evaluated different cancers separately, they did observe a modest reduction in breast cancer with an incidence rate ratio of 0.77 (95% CI:0.43; 1.40) [ 91 ]. The use of metformin after a cancer diagnosis has also been shown to decrease the risk of breast cancer-specific death [ 92 ]. An early meta-analysis of observational studies found that metformin decreased breast cancer risk in postmenopausal women with diabetes compared to those on other antidiabetic therapies [ 11 ].…”
Section: Translating Metformin To the Clinicmentioning
confidence: 99%
“…Significantly, several observational studies have consistently shown a decreased risk of breast cancer and lower recurrence rates among individuals who are overweight and/or have T2DM and use metformin [122,123]. Metformin emerges as a significant player associated with improved disease-free survival (DFS) and overall survival (OS), suggesting its potential positive impact on survival outcomes among invasive breast cancer patients with T2DM [124]. In addition, a meta-analysis of 31,031 breast cancer patients suggests a potential benefit of metformin therapy, showing reductions in all-cause mortality and progression-free survival compared with non-metformin users [125].…”
Section: Clinical Studiesmentioning
confidence: 99%